Ecological implication of changing irrigation sources and farming practices: experiences from West Bengal, India - Amartya Pani; Pulak Mishra; Mrinal Kanti Dutta (Discover Agriculture)
Abstract It is widely acknowledged that the agrarian nature of rural economy, combined with policy biases and institutional limits, has contributed to low productivity and slow growth in the Indian agriculture sector. With changing climate and market conditions, the Indian agriculture sector requires an adequate transition in cropping patterns to ensure the sector's viability and the inclusion of land-constrained farmers in the intensification process. The necessity for crop pattern shift has been emphasized further. Besides, input-intensive agricultural practices have resulted in biodiversity losses, groundwater depletion, and soil degradation, raising severe worries about the sector's sustainability, particularly in rainfed areas. This study carried out in the setting of West Bengal, India, which has a substantial population of land-constrained farmers. The objectives of the study include examining the changes in irrigation sources and cropping practices, understanding their implications for the agriculture sector with its local ecology, and assessing the role of the local level institutions in management and use of irrigation facilities and conservation of natural resources. Using standard descriptive statistics from various secondary sources for the period 2004–05 to 2014–15, graphical techniques and policy review the paper identifies crop diversification, crop concentration, cropping intensification, sources of irrigation, fertilizer use, rainfall pattern, and changes in wetland area as the major drivers of the agrarian transition in favor of non-food grains. The study, therefore, suggests that initiatives should be taken for guiding the farmers towards appropriate farming practices for judicious use of water and other natural resources. Moreover, the findings appear to point to the need for additional infrastructure development, they also provide insights into designing organic and more resilient policies and institutions to promote ecology-centric participatory irrigation and farming practices for the long-term growth of agrarian sectors.